PERLINDUNGAN HUKUM TERHADAP PEMEGANG SERTIPIKAT TANAH PENGGANTI KARENA HILANG - Lenny Maulani Maulani (Universitas Negeri Semarang, 2021)
A certificate of land rights is a proof of right that is very strong. With the issuance of a certificate, a person can easily prove that he is the holder of land rights. But what if the certificate is lost. In such circumstances it is possible to issue a replacement certificate. We will discuss how the procedure for issuing a replacement certificate for lost replacement certificate and legal protection for the holder of a lost replacement certificate. The research method used in this journal is a normative juridical research method or a statutory approach. The results of this research, if the certificate is lost, can apply for a replacement certificate to the local Regency / City Land Office in accordance with the applicable procedure. Legal protection for replacement certificate holders is the same as for first-time registration certificates. Because after the issuance of the replacement certificate, the lost certificate is canceled. So that the lost certificate is no longer valid.